Improving Conceptual Understanding of Eleventh Grade Students on Colloid Topic Using Multimedia - Assisted Probing - Prompting - Oktaviyanti, Dita Try; Wardani, Sri; Kurniawan, Cepi (Postgraduate, Universitas Negeri Semarang, Indonesia, 2018)
This study aims to determine the effect of interactive multimedia-assisted probing - prompting learning model on conceptual understanding of students. Population in this study was the students of class XI of State SHS 11 Semarang academic year 2017/2018. Sampling was done by purposive sampling technique and obtained three classes as the samples namely class XI-Science 1 and class XI-Science 4 as the experiment classes, and class XI-Science 3 as the control class. The study method used was mix methods with Sequential Transformative Strategy model. The study data were obtained by test and observation methods. The results showed that Interactive multimedia-assisted probing-prompting learning model had an effect on students’ conceptual understanding with percentage improvement in two experimental classes of 24.15% and 15.12%, respectivelly.